1995
DOI: 10.1002/qj.49712152610
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of climate change over europe using a nested regional‐climate model. I: Assessment of control climate, including sensitivity to location of lateral boundaries

Abstract: SUMMARYPresent-day climate simulations for Europe are presented, based on a SO km regional-climate model (RCM) driven by output from a global general-circulation model (GCM) using a one-way nesting approach. Both models are components of the Meteorological Office Unified Forecast/Climate Model and use the same subgrid-scale physics. The relationship between the RCM circulation and that of the driving GCM was assessed in seasonal RCM integrations using domains of different sizes. In the larger domains, both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
316
2
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 326 publications
(346 citation statements)
references
References 42 publications
13
316
2
5
Order By: Relevance
“…For most seasons and regions the models agree fairly well with observations out to about the 95th percentile, though the models' frequencies at this intensity tend to be less. The shortfall appears to be due in part to resolution, which limits the strength of upward motions that produce precipitation, either by direct uplift or by helping to trigger convection (e.g., Jones et al 1995;Gutowski et al 2003). The resolutions used also limit the models' ability to depict small-scale convective events (e.g., Gutowski et al 2003;Biasutti et al 2006).…”
Section: Simulated Precipitation Intensity Distributions a Comparisomentioning
confidence: 99%
“…For most seasons and regions the models agree fairly well with observations out to about the 95th percentile, though the models' frequencies at this intensity tend to be less. The shortfall appears to be due in part to resolution, which limits the strength of upward motions that produce precipitation, either by direct uplift or by helping to trigger convection (e.g., Jones et al 1995;Gutowski et al 2003). The resolutions used also limit the models' ability to depict small-scale convective events (e.g., Gutowski et al 2003;Biasutti et al 2006).…”
Section: Simulated Precipitation Intensity Distributions a Comparisomentioning
confidence: 99%
“…In a limited area, RCMs thus respond physically consistent to external forcings whilst resolving important meso-scale atmospheric processes such as orographic enhancement/supression of precipitation, and development of frontal systems [Jones et al, 1995]. Thus, the physical mechanisms responsible for individual precipitation events and intensities are more realistically described than in a typ- …”
Section: Introductionmentioning
confidence: 96%
“…For this variable it has been shown that RCMs are able to add significant information to the driving global simulations, both in space and time (e.g., Jones et al 1995;Durman et al 2001;Jones et al 2004). In general terms, the RCMs produce an intensification of precipitation with respect to the driving global climate model (GCM), related to the intensification of the hydrological cycle (Jones et al 1995;Durman et al 2001;Buonomo et al 2007). Lynn et al (2010) tested a regional climate model with different physics components at two different spatial resolutions.…”
Section: Introductionmentioning
confidence: 99%